(untitled) (International journal of medical sciences, 2026)
This review article examines the social and hygienic aspects of the health of children with disabilities from the perspective of preventive medical care and public health. It analyzes current data on the impact of socioeconomic conditions, family environment, access to medical care, and educational institutions on the health of this group of children. Particular attention is paid to the role of environmental factors, upbringing conditions, and lifestyle in the development of chronic diseases and functional disorders. Research findings indicating the increased vulnerability of children with disabilities to adverse social and hygienic influences are summarized. The importance of a comprehensive interdisciplinary approach, including medical, social, and preventive measures aimed at improving the quality of life and strengthening the health of children with disabilities, is emphasized.